Unroofed coronary sinus in a patient with neurofibromatosis type 1 - Luciano Pereira Bender; Maria Rita F. Meyer; Rafael Fabiano M. Rosa; Rosana Cardoso M. Rosa; Patrícia Trevisan; Paulo Ricardo G. Zen (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To report the uncommon association between neurofibromatosis type 1 (NF1) and unroofed coronary sinus. CASE DESCRIPTION: Girl with four years and six months old who was hospitalized for heart surgery. The cardiac problem was discovered at four months of life. On physical examination, the patient presented several café-au-lait spots in the trunk and the limbs and freckling of the axillary and groin regions. Her father had similar skin findings, suggesting the NF1 diagnosis. The cardiac evaluation by echocardiography disclosed an atrial septal defect of unroofed coronary sinus type. This cardiac finding was confirmed at surgery. The procedure consisted of the atrial septal defect repair with autologous pericardium. COMMENTS: NF1 is a common autosomal dominant disorder caused by mutations in the NF1 gene. Among the NF1 findings, congenital heart defects are considered unusual. In the literature review, there was no association between NF1 and unroofed coronary sinus, which is a rare cardiac malformation, characterized by a communication between the coronary sinus and the left atrium, resultant from the partial or total absence of the coronary sinus roof. It represents less than 1% of atrial septal defect cases. More reports are important to determine if this association is real or merely casual, since NF1 is a common condition.